(untitled) (BIRDEM Medical Journal, 2017)
Background: Primary hyperparathyroidism (PHPT) is associated with either an adenoma or hyperplasia of chief cells of the parathyroid gland. It may occur sporadically, as a single autosomal dominant familial disorder, or as a part of the autosomal dominantly transmitted complex of multiple endocrine neoplasia (MEN). PHPT is relatively rare in children and adolescents. It is a condition characterized by an inappropriate excess of parathyroid hormone (PTH) secretion. Method: This study was carried out in the Department of Otolaryngology and Head-Neck Surgery, BIRDEM General Hospital, Dhaka, Bangladesh from July 2009 to June 2015. A total 35 patients of different age group of both sex were included in this study. Preoperative localization test, including sestamibi scan, ultrasound or both were done for all patients. Result: The total number of patients were 35 which included 19 males (54.29%) and 16 females (45.71%). The age of the patients varied from 18 to 65 years (average 40.90 years). All of these patients underwent operative removal of the adenoma. Serum PTH levels were above normal (>53 pg/ml) in all patients and ranged from 65 to 700 pg/ml. Serum calcium levels were above normal (>11 mg%) in most cases and ranged from 10.4 to 14.8 mg%. In our study, 25 patients (71.42%) had high calcium levels with the ten cases were at upper normal. Serum phosphate (PO4) levels were on an average 1.8 (lower normal). In view of the raised calcium levels, the PTH was estimated followed by either sonography or CT scan. Serum PTH levels (85-700 pg/ml) were very high in 18 cases, high in 11 cases (65-85 pg/ml) and upper normal in 6 cases (59-64). In our study after operation, 13 patients developed hypocalcaemic state and required intravenous calcium at operation day and first post operative day, and rest of the patients hypocalcaemic state corrected by oral calcium supplement. In our study temporary hypocalcaemia was very common and reported recurrent laryngeal nerve injury was less than one percent. Conclusion: In parathyroid adenoma bone resorption causes recurrent bone fractures leading to a crippling condition. Preoperative localization of parathyroid adenoma with the help of sestamibi scan, surgical expertise need to remove the tumor and post operative calcium level management with the help of endocrinology department are necessary for successful management of parathyroid adenoma. Birdem Med J 2017; 7(2): 138-142